A review of evolution of electrospun tissue engineering scaffold: From two dimensions to three dimensions - Ngadiman, N.; Noordin, M.; Idris, A.; Kurniawan, Denni (Sage Publications, 2017)
The potential of electrospinning process to fabricate ultrafine fibers as building blocks for tissue engineering scaffolds is well recognized. The scaffold construct produced by electrospinning process depends on the quality of the fibers. In electrospinning, material selection and parameter setting are among many factors that contribute to the quality of the ultrafine fibers, which eventually determine the performance of the tissue engineering scaffolds. The major challenge of conventional electrospun scaffolds is the nature of electrospinning process which can only produce two-dimensional electrospun mats, hence limiting their applications. Researchers have started to focus on overcoming this limitation by combining electrospinning with other techniques to fabricate three-dimensional scaffold constructs. This article reviews various polymeric materials and their composites/blends that have been successfully electrospun for tissue engineering scaffolds, their mechanical properties, and the various parameters settings that influence the fiber morphology. This review also highlights the secondary processes to electrospinning that have been used to develop three-dimensional tissue engineering scaffolds as well as the steps undertaken to overcome electrospinning limitations.